Resistance exercise combined with protein supplementation for skeletal muscle mass in people with pancreatic cancer undergoing neoadjuvant chemotherapy: Study protocol for the REBUILD trial - Paola Gonzalo-Encabo; John Gardiner; Mary K. Norris; Rebekah L. Wilson; Amber J. Normann; Danny Nguyen; Nathan Parker; Darryl Tjogas; Lauren K. Brais; Jeffrey A. Meyerhardt; Michael H. Rosenthal; Brian M. Wolpin; et al. (PLoS ONE, 2025)
Background Pancreatic cancer patients’ prognosis may be limited by two conditions, cachexia and sarcopenia. Resistance exercise and protein supplementation are safe non-pharmacological strategies that may increase or preserve skeletal muscle mass within this population. Therefore, the primary aim of this study is to examine the feasibility of a home-based virtually supervised resistance exercise intervention, with or without protein supplementation in pancreatic cancer patients initiating neoadjuvant chemotherapy. This intervention may also maintain skeletal muscle mass and improve plasma biomarkers associated with muscle tissue wasting, physical function and psychological measures. Methods We aim to recruit 45 patients with locally advanced pancreatic cancer initiating neoadjuvant chemotherapy. Patients will be randomized to receive either Resistance Exercise (RE) (n = 15), Resistance Exercise and Protein Supplementation (RE + PS) (n = 15), or Attention Control (AC) (n = 15). Patients randomized to RE or RE + PS will receive 16-weeks of home-based virtually supervised resistance exercise. The AC will receive a 16-week stretching program. Primary and secondary outcomes will be measured at baseline and after 16 weeks during study visits. Discussion The REBUILD trial is the first randomized controlled trial that combines resistance exercise with daily protein supplementation during neoadjuvant chemotherapy in pancreatic cancer patients. Our novel home-based virtually supervised exercise intervention seeks to mitigate barriers to participation in this vulnerable population. Furthermore, results of this trial will address important research gaps associated with pancreatic cancer-related cachexia, a condition closely connected with poor prognosis and mortality.